High-repetition rate attosecond beamline for multi-particle coincidence experiments - Srinivas, Hemkumar; Shobeiry, Farshad; Bharti, Divya; Pfeifer, Thomas; Moshammer, Robert; Harth, Anne (Optics express, 2022)
In this paper, a 3-dimensional photoelectron/ion momentum spectrometer (reaction microscope) combined with a table-top attosecond beamline based on a high-repetition rate (49 kHz) laser source is presented. The beamline is designed to achieve a temporal stability below 50 attoseconds. Results from measurements on systems like molecular hydrogen and argon dimers demonstrate the capabilities of this setup in observing the attosecond dynamics in 3D while covering the full solid angle for ionization processes having low cross-sections.
Gesehen am 13.05.2022